المحاسبة الالكترونية ودورها في تحقيق التمثيل الصادق للمعلومات المحاسبية - امشهر ابراهيم ،علي حمد (جامعة الوادي University of Eloued, 2025)
هدفت الدراسة إلى تحليل دور المحاسبة الإلكترونية في تحقيق التمثيل الصادق للمعلومات المحاسبية. اعتمدت الدراسة على المنهج الوصفي التحليلي، واستخدمت استمارة استبانة لجمع البيانات من العاملين في مصرف الوحدة، ممن لهم علاقة مباشرة بموضوع الدراسة، مثل مدراء الفروع ورؤساء الأقسام والمراجعين الداخليين والمحاسبين والإداريين. تم توزيع 120 استبيانًا، واسترجع منها 102 استمارة، بنسبة استرجاع بلغت 85%. توصلت الدراسة إلى عدة نتائج، منها وجود علاقة ذات دلالة إحصائية بين كفاءة وفاعلية المحاسبة الإلكترونية وتحقيق التمثيل الصادق للمعلومات المحاسبية في مصرف الوحدة الرئيسي بطرابلس. كما وجدت علاقة ذات دلالة إحصائية بين شمولية المعلومات التي تقدمها أنظمة المحاسبة الإلكترونية وتحقيق التمثيل الصادق للمعلومات المحاسبية. أثبتت الدراسة أيضًا وجود علاقة بين الأمان والامتثال في أنظمة المحاسبة الإلكترونية وتحقيق التمثيل الصادق للمعلومات المحاسبية. أظهرت الدراسة كذلك وجود علاقة بين التقارير المالية الفورية ودقتها في تقديم المعلومات المحاسبية وتحقيق التمثيل الصادق في مصرف الوحدة الرئيسي بطرابلس The study aimed to analyse the role of electronic accounting in achieving a faithful representation of accounting information. The study adopted a descriptive and analytical approach, and used a questionnaire to collect data from Al Wahda Bank employees who are directly related to the subject of the study, such as branch managers, department heads, internal auditors, accountants, and administrators. A total of 120 questionnaires were distributed and 102 questionnaires were returned, with a return rate of 85%. The study found several findings, including the existence of a statistically significant relationship between the efficiency and effectiveness of e-accounting and achieving a faithful representation of accounting information at Al Wahda Main Bank in Tripoli. It also found a statistically significant relationship between the comprehensiveness of information provided by eaccounting systems and the achievement of truthful representation of accounting information. The study also proved that there is a relationship between security and compliance in electronic accounting systems and achieving a faithful representation of accounting information. The study also showed that there isa relationship between real-time financial reporting and its accuracy in providing accounting information and achieving truthful representation at Al Wahda Main Bank in Tripoli..
E-accounting and its role in achieving a faithful representation of accounting information (A field study on Al Wahda Bank in Tripoli and its branches in the western region-2022-2024)
Keywords: المحاسبة الالكترونية; التقارير الفورية; الأمان والامتثال; شمولية المعلومات; التمثيل الصادق; E-accounting; real-time reporting; security and compliance; comprehensiveness of information; honest representation